2021
DOI: 10.1111/nhs.12854
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers’ distress and perceived discrimination related to COVID‐19 in Colombia

Abstract: This study examined the association of perceived discrimination related to COVID‐19 with psychological distress in healthcare workers in the Colombian Caribbean region. The authors designed and conducted a cross‐sectional study, recruiting a non‐probabilistic sample by email or instant messaging. Participants filled out a questionnaire including scales for perceived discrimination, anxiety, depression, perceived stress related to COVID‐19, and suicide risk. Healthcare workers ( n = 150) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 26 publications
2
26
1
3
Order By: Relevance
“…However, Mahmoudi et al (2021) , in COVID-19 survivors, documented that internalized stigma scores were statistically significantly associated with scores for insomnia and post-traumatic stress disorder. Likewise, Campo-Arias et al (2021) observed, in health workers (nursing assistants and doctors), that a measure of perceived discrimination showed a significant positive correlation with depressive symptoms. Discrimination represents an additional critical stressor in any context ( Meyer, 2003 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, Mahmoudi et al (2021) , in COVID-19 survivors, documented that internalized stigma scores were statistically significantly associated with scores for insomnia and post-traumatic stress disorder. Likewise, Campo-Arias et al (2021) observed, in health workers (nursing assistants and doctors), that a measure of perceived discrimination showed a significant positive correlation with depressive symptoms. Discrimination represents an additional critical stressor in any context ( Meyer, 2003 ).…”
Section: Discussionmentioning
confidence: 88%
“…In healthcare workers, Zandifar et al (2020) , in 894 participants in Iran, observed a high correlation between perceived stigma and post-traumatic stress scores. In Colombia, Campo-Arias et al (2021) , in 150 health workers, found that scores on perceived discrimination were positively correlated with scores on depressive symptoms among nursing assistants and physicians.…”
mentioning
confidence: 99%
“…On a dichotomous scale (1 as yes, 0 as no), a higher sum score represented higher perceived stigma of being a healthcare worker. A similar scoring method was also used in another study measuring perceived stigma among healthcare workers in Columbia (Campo-Arias et al, 2021). We conducted a supplementary exploratory factor analysis to examine the dimensionality of the items.…”
Section: Perceived Stigmamentioning
confidence: 99%
“…The study of stress focuses on the identification of environmental stressors, subjective perceptions, affective cognitive-behavioural reactions, and physiological responses ( Lee, 2012 ). One of the most recognized instruments for evaluating psychological stress is the Perceived Stress Scale (PSS), which has been adapted for the current epidemiological context ( Campo-Arias et al, 2021 ). PSS focuses on how individuals perceive stress, which reflects an imbalance between situational demands and the resources to cope with it ( Chiu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%